Asymptomatic congenital tracheal stenosis - Sumi, Toshiyuki (Respirol Case Rep, 2019)
Congenital tracheal stenosis (CTS) is often identified by characteristic wheezes and cyanosis in childhood. However, an asymptomatic progression to adulthood is rare. Asymptomatic latent CTS cases with a mild degree of stenosis may exist.